New Types of Perfectly Supra Continuous Functions - Humadi, Nadia Kadum; Ali, Haider Jebur (Iraqi Journal of Science, 2020)
We wrote this paper to proffer new types of the perfectly supra continuous functions. We also introduced new types of supra continuous, supra open and supra closed functions.